Emission dynamics of hybrid plasmonic gold/organic GaN nanorods. (24th November 2017) - Mohammadi, F; Schmitzer, H; Kunert, G; Hommel, D; Ge, J; Duscher, G; Langbein, W; Wagner, H P
Abstract: We studied the emission of bare and aluminum quinoline (Alq3 )/gold coated wurtzite GaN nanorods by temperature- and intensity-dependent time-integrated and time-resolved photoluminescence (PL). The GaN nanorods of ∼1.5 μ m length and ∼250 nm diameter were grown by plasma-assisted molecular beam epitaxy. Gold/Alq3 coated GaN nanorods were synthesized by organic molecular beam deposition. The near band-edge and donor-acceptor pair luminescence was investigated in bare GaN nanorods and compared with multilevel model calculations providing the dynamical parameters for electron–hole pairs, excitons, impurity bound excitons, donors and acceptors. Subsequently, the influence of a 10 nm gold coating without and with an Alq3 spacer layer was studied and the experimental results were analyzed with the multilevel model. Without a spacer layer, a significant PL quenching and lifetime reduction of the near band-edge emission is found. The behavior is attributed to surface band-bending and Förster energy transfer from excitons to surface plasmons in the gold layer. Inserting a 5 nm Alq3 spacer layer reduces the PL quenching and lifetime reduction which is consistent with a reduced band-bending and Förster energy transfer. Increasing the spacer layer to 30 nm results in lifetimes which are similar to uncoated structures, showing a significantly decreased influence of the gold coating on the excitonic dynamics.